2008
DOI: 10.1016/j.ejvs.2008.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Automated and Manually Measured Toe Blood Pressure in Ischemic Legs of Diabetic Patients

Abstract: The automatic TBP device is reliable for measuring low pressures and thus for exclusion of critical limb ischemia in patients with diabetes. After algorithm adjustment the device's reliability appears to be acceptable in the entire spectrum of TBP values. TBP appears to have less inter and intraobserver variability than what is reported for ABP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Påhlsson et al found a mean intraobserver variability of 2e3 mmHg for toe pressure measurements in a small study (n ¼ 16) with diabetic patients using nurses and vascular technologists as observers. 9 Another study showed LoA for 1-week reproducibility of LDF measurements of approximately AE30 mmHg. 6 Combined with the findings in our study, observer variation in curve readings is likely to be an important factor in reproducibility.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Påhlsson et al found a mean intraobserver variability of 2e3 mmHg for toe pressure measurements in a small study (n ¼ 16) with diabetic patients using nurses and vascular technologists as observers. 9 Another study showed LoA for 1-week reproducibility of LDF measurements of approximately AE30 mmHg. 6 Combined with the findings in our study, observer variation in curve readings is likely to be an important factor in reproducibility.…”
Section: Discussionmentioning
confidence: 98%
“…Påhlsson et al proposed the frequent presence of biphasic curve patterns in LDF toe pressure measurements as a potential source of variation, as they can be difficult to interpret. 9 Based on findings in earlier animal and clinical studies, they hypothesised that this could be attributed to the response to post-occlusive reactive hyperaemia in the presence of the combination of a vascular stenosis along with a normal capillary bed. The normal response to reactive hyperaemia following arterial occlusion, such as during segmental pressure measurement, is brief vasodilation followed by vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the device tested in this study, a number of other automatic and semi-automatic portable devices based on photoplethysmographic principles have been developed for practical and cost-effective toe-pressure measurements. 41,103,104,170 These devices have all been compared to standardised distal pressure assessments with varying success. Generally, prior studies have failed to follow recommendations for diagnostic accuracy studies as outlined by STARD and Cochrane DTA, especially regarding patient selection and disease classification.…”
Section: Discussionmentioning
confidence: 99%
“…64 Important factors compromising reproducibility include observer variation 170 , temperature control 96 , occlusion cuff size 100 and positioning 101 , and the interpretation of the derived signal. 104,169 The important influence of short-term biological variation, for instance, caused by alterations in haemodynamics and vasospasm, is revealed by the substantial improvement in agreement between methods when conducting measurements simultaneously as opposed to subsequently. 64,75 A mean day-to-day variation for the SGP method (standard deviation of mean pressure differences) ranging from 6-10 mmHg for toe pressures and 9-11 mmHg for ankle pressures has been reported.…”
Section: Variation In Distal Pressure Measurementsmentioning
confidence: 99%